PATHOHISTOLOGICAL AND IMMUNOHISTOCHEMICAL FEATURES OF PROSTATIC CANCER - Крутенко, О.В. (World of Medicine and Biology, 2016)
Prostate cancer (PC) is one of the most common cancers, which is about 12% in the structure of morbidity men and ranks second in the structure of mortality from malignant neoplasm. Diagnosis of PC based on the determination of prostate-specific antigen (PSA) in blood serum and pathological study of intraoperative and biopsy material. There are several histological types of PC. The most common form is acinar cell carcinoma (ACC), which occurs in 95% of all cases of prostate cancer, and ductal adenocarcinoma (DAC) of the prostate gland, which is about 1% of all prostate cancer. Histological and immunohistochemical (IHC) features of various forms of prostate cancer have been studied insufficiently. The aim of the research was to determine the histopathological and immunohistochemical features of PC. Material and methods. The comprehensive research conducted on postoperative material of 40 patients aged 52 to 75 years, with histopathological verified diagnosis of PC. Microscopic examination of histopathological slides defined histological type of tumor and evaluate the degree of malignancy Gleason system. IHC studies were performed using primary monoclonal antibody against Ki-67 Antigen, AMACR, CK HMW, PSA and AR. Statistical analysis included calculation of mean value (M) and standard deviation (σ). Probability differences comparable values were determined by Student’s t test (T); results considered likely at p